Jurisprudential and legal disagreement about the adaptation of the crime of transmitting the infection of the Covid 19 virus - Bouezzit, Nada (Journal of Human Sciences, 2022)
The crime of transmitting infection is one of the new crimes imposed by scientific and technological developments. There are a number of forms of intentional wrong behavior that can transmit infection or injury to others, and its perpetrators can evade punishment, due to the absence of specific legal texts and the accuracy of this crime.